R Strauss four last songs; Wa Mozart, piano concerto no. 20 in D minor K466**; Sergie Prokofiev, Romeo and Juliet [sound recording] - Strauss, Richard; Mozart, Wolfgang; Prokofiev, Sergie; DDD Stereo; BBC MM270. (BBC Music, 2006)
Struss: four last songs, Im Abendrot (track 4) Glowing orchestral colours introduce the final song in which an elderly couple watch the sun set and ponder on approaching death. The sky is empty except for two larks, represented by distand woodwind twitterings. They reappear as the music draws to its close. In the extended coda for orchestra alone, the transfiguration theme from Death and Transfiguration is heard (6:16), the mood perfectly relaxed. Death is accepted and even welcomed.
Mozart: piano concerto no. 20, rondo finale (Track 7) Even as the 1785 premiere got under way, the copyist was writing out the parts for the finale. So, with the ink barely dry on the manuscripts paper, Mozart launch into the Rondo's opening theme. A cat and mouse affair, with scurrying strings and seeming changes of direction, it just refuses to settle. Sfter a brief cadenza, oboe, bassoon and horns repeat the perky second theme (6:000, this time in D major. From then on all is sunshine as piano and orchestra sprint to the finishing line.
Prokofiev: Romeo and Juliet, Mpntagues and Capulets (Track 8) This contains one of Prokofiev's best known themes, full swaggering arrogance. The middle section (2:28) is in marked contrast, as light as chamber of music, with Kandinsky-like flecks of colour from woodwind and soft percussion.
Death of Tybalt (Track 12) An orchestral showpiece, projected on its way with frantic string semiquavers, punctuated by stabbing brass and percussion. Fourteen intimidating chords (2:15) reach a hight which in turn heralds a brassy climax full of screaming trumpets. On stage, tempo considerations have to be made for the dancers but in the concert hall the orchestra can be given its head.
Sergie Prpkofiev: Romeo and Juliet (excerps from the concert suites), Montagues and capulets (04:41); Romeo and Juliet before parting (06:44); Aubade (02:26); Dance of the Antilles Girls (02:26); Death of Tybalt (05:04)
Bridgewater Hall 10th anniversary CD
Tracks 1-4 recorded live at the Bridgewater Hall, Manchester on 6 May 2004; Producer: Martin Cotton; Engineer: Stephen Rinker
Tracks 5-7 recorded live at the Bridgewater Hall, Manchester on 24 March 2006; Producer: Paul Hindmarsh; Engineer: Stephen Rinker
Tracks 8-12 recorded live at the Bridgewater Hall, Manchester on 11 December 2004; Producer: Mike George; Engineer: Stephen Rinker
Schwanewilms, Anne, Soprano
Stott, Kathryn, piano
Keywords: Classical Music; Orchestra music; Piano music